Assessing quality and biases in ethnomathematics-based numeracy worksheets: A Many-Facet Rasch Model analysis - Rahmi Ramadhani; Soeharto Soeharto; Fitria Arifiyanti; Rully Charitas Indra Prahmana; Alfa Saleh; Zsolt Lavicza (Social Sciences and Humanities Open, 2025)
Numeracy is a vital 21st-century skill, enabling students to solve problems relevant to socio-cultural contexts, a significance emphasized by international assessments such as PISA. Teachers can improve students' numeracy abilities by creating teaching materials that incorporate diverse activities to address daily problems through cultural lens (ethnomathematics) within a sociocultural framework. Students’ worksheets are considered effective tools for this purpose. Therefore, this study aimed to investigate numeracy learning activities in ethnomathematics-based worksheets within socio-cultural contexts using Many-Facet Rasch Model analysis. To achieve this objective, ten raters evaluated four learning activities based on five criteria: relevance, feasibility, construction and systematics, appearance, and language appropriateness. A total of 200 data points were coded in the FACETS software and subsequently analyzed. The results confirm that the worksheets meet educational quality standards in terms of both validity and reliability. Language appropriateness was the most challenging criterion for raters, whereas construction and systematics were the easiest. In addition, Rater A was the strictest, while Rater J was the most lenient. The evaluation also confirmed gender bias in Learning Activity 2 and educational background bias in Learning Activity 3.